High-frequency ecological momentary assessment of emotional and interpersonal states preceding and following self-injury in female adolescents - Koenig, Julian; Blanke, Julia; Parzer, Peter; Santangelo, Philip S.; Resch, Franz; Ebner-Priemer, Ulrich; Kaess, Michael (European child & adolescent psychiatry, 2021)
Non-suicidal self-injury (NSSI) is a considerable health problem among adolescents. Affect regulation by means of self-injury may promote the maintenance of NSSI. However, existing findings have limited ecological validity. The present study aimed to assess emotional and interpersonal states preceding and following incidents of NSSI in female adolescents. Adolescents with NSSI-disorder completed ecological momentary assessments of affective and interpersonal states on an hourly basis for multiple days. Multilevel mixed-effect regression analyses were conducted to assess antecedences and consequences of acts of self-injury. Data from n = 73 female adolescents covering a total of 52 acts of self-injury were available for analyses. The urge to self-injure on the between subject-level and negative affect on the within-level were best predictors of self-injury. Surprisingly, self-injury increased negative affect and decreased feelings of attachment (mother only) in the following hour. In line with findings in adults, results illustrate the important association between negative affect and self-injury in female adolescents. However, the occurrence of NSSI itself was related to concurrent increases in negative affect, and even prospectively predicted a consecutive increase in negative affect. Therefore, improvements of negative affect following (or during) self-injury, as previously reported, are at best short-lived (< 1 h).